AN ANTIDOTE TO COMPASSION FATIGUE: DIRECT CARE STAFF USING CALM FOR ASSISTED LIVING RESIDENTS. (11th November 2018) - Woods, D; Phillips, L; Johnson, R; Knox, V
Abstract: Behavioral symptoms of dementia (BSDs) such as restlessness, agitation, aggressive behavior, yelling, and nighttime awakenings, exhibited by more than 85% of those with dementia, result in distress for the person with dementia (PWD) and avoidance in caregivers. Direct care staff (DCS) who work with residents exhibiting BSD frequently find themselves with limited tools at their disposal to alleviate these behaviors. Over time DCS may experience compassion fatigue. Teaching direct care staff (DCS) calming interventions (CALM), specifically therapeutic touch and the use of therapeutic communication skills, may promote social "bonding" between residents and staff, strengthen relationships, decrease compassion fatigue, and improve the quality of care. DCS training was completed over 4 months. Seven of 10 DCS completed the study. Five 0f 7 (71%) showed an increase in mutuality indicating increased social bonding. Specific items showing an increase were "How well do you think you are prepared to take care of the resident's emotional needs?" "How well prepared do you think you are for the stress of caregiving?" and "How well prepared do you think you are to make caregiving activities pleasant?" Interview data supported positive experiences of relaxation for the DCS and an observed decrease in BSD for the residents compared to baseline. This pilot study provides beginning evidence for the effect of CALM on the DCS, increasing mutuality with PWD and improving quality of care. Especially pertinent in the mutuality scores are those related to questions of being able to manage the stress of caregiving, and thus decrease compassion fatigue.